Investigation of electrical activity of hypothalamic arcuate nucleus cholinergic neurons in fasting and fed state in ChAT-Cre transgenic mice (Annals of Medical Research, 2023)
Aim: The hypothalamus consists of many subnuclei and contains neural pathways that play a significant role in feeding behavior. Cholinergic neurons in the basal forebrain have been shown to be involved in satiety activation during feeding, but the effect of hypothalamic cholinergic neurons on food intake is unclear. The aim of this study was to use optogenetics to examine the synaptic connections and electrophysiological features of acetyltransferase (ChAT) neurons in the hypothalamic arcuate nucleus (ARC), a region largely associated with feeding behavior, during fasting and satiety.Materials and Methods:  Fifteen (aged between 4-6 weeks)  ChAT-Cre male mice were used in all experiments. Adeno-associated virus (AAV-GFP) was injected to specifically label ChAT neurons localized in the hypothalamic arcuate nucleus. In addition, AAV-ChR2 virus was injected for optogenetic experiment to determine the synaptic connection of these neurons with neighboring neurons. Then, fasting and fed mice were decapitated for electrophysiology recordings.Results:  Our results showed that the firing frequency in ARC-ChAT neuron recordings from fed mice was significantly higher than in fasted mice (p
Keywords: ChAT neurons; Hypothalamus; Electrophysiology; Optogenetics